PENGALAMAN PEREMPUAN DENGAN PERSALINAN PERVAGINAM DI USIA DINI DI DESA MAMBU TAPUA DAN BA’BA TAPUA DI WILAYAH KERJA PUSKESMAS MATANGNGA - Masniati Masniati; Musniati Musniati; Immawanti Immawanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study is to gain an understanding and explore in-depth the experiences of women with vaginal birth at an early age. The research design used is qualitative research with a phenomenological approach. The number of participants as many as five participants with different characteristics. Data collection through in-depth interviews that were analyzed using the Miles and Huberman model. Results: The experience of women with vaginal birth at an early age in the working area of the Matangnga puskesmas, showed a change in various aspects, namely the experience of women before delivery, perceptions of changes in postnatal lifestyle, the impact of early marriage, the role of health workers in health services, expectations for health services. Suggestions include: paying more attention to early-age couples who are pregnant or those who have given birth, giving counseling to women who are pregnant and giving birth at an early age, making local government or village regulations related to early marriage, further research, and input to maternity nursing programs.